Measurement through structural equations of the self-concept instrument in high-school students - Sabando-García, Angel Ramón; Jiménez-Bustillo, Oswaldo José; Llacsa-Puma, Lidia Janeth; Castro-Castillo, Graciela Josefina; Moreira-Choez, Jenniffer Sobeida; Rengifo-Lozano, Raúl Alberto (Frontiers in Education, 2025)
IntroductionSelf-concept is a fundamental component of psychological and educational development, playing a critical role in students' academic performance and emotional wellbeing. Despite its importance, gaps remain in the validation of measurement instruments tailored to specific educational contexts.MethodsThis study employed a quantitative, predictive, and correlational methodology with a non-experimental cross-sectional design. A total of 172 adolescents from grades 8, 9, and 10 in a school in Santo Domingo, Ecuador, were selected through non-probabilistic convenience sampling. The Self-Concept Questionnaire FORM-5 (AF-5), which evaluates academic/occupational, social, emotional, family, and physical self-concepts, was administered. Data analysis utilized SPSS version 25 and AMOS 24 software to ensure reliability and validity through structural equation modeling.ResultsThe AF-5 demonstrated high reliability, with a Cronbach's alpha of 0.854. Gender differences were observed, with females scoring higher in emotional self-concept and males excelling in physical self-concept. Structural equation modeling confirmed the instrument's significant factor loadings, validating its application in measuring self-concept.DiscussionThe findings highlight the robustness and applicability of the AF-5 in educational contexts, providing a validated tool to assess self-concept dimensions among upper elementary students. The study underscores the importance of using reliable instruments to better understand and support students' academic and emotional development. Further research is recommended to explore the instrument's application across diverse populations.